TEACHING ENGLISH GRAMMAR IN ASIAN CONTEXTS making meaning with grammar. - Xavier, Christine Anita; Chia, Alexius ([S.l.] : ROUTLEDGE, 2025)
This book guides teachers, teacher educators and pre-service student teachers on using grammar as a pedagogical tool for meaning making, linking grammar as a meaning-making resource to literacy development. When grammar is meaningfully linked to literacy skills such as reading and writing, there is contextualised teaching of grammar. The authors thoroughly explore key concepts in grammar, including grammar as structure and grammar as choice. They illuminate these concepts by analysing a range of authentic texts from Asian contexts, showing how specific grammar features are purposefully used to convey meaning. Examples and illustrations of teaching ideas and materials focusing on contextualised teaching of grammar, including lesson plans, activity outlines, worksheets and teaching strategies, are contributed by current teacher practitioners who have tried out these ideas in their language classes. These teacher practitioners also share their reflections on how these ideas have worked in their classes. As a result, this book is an indispensable resource for teachers, teacher educators, pre-service teachers of English as both a first language and a second or foreign language, as well as anyone who is interested in harnessing the power of grammar to enhance English language teaching and literacy development.
Keywords: English language -- Grammar -- Study and teaching; English language -- Study and teaching -- Foreign speakers; LANGUAGE ARTS & DISCIPLINES / Grammar; LANGUAGE ARTS & DISCIPLINES / Study & Teaching